Practice patterns of adjunctive therapy for venous leg ulcers. (February 2017) - Aziz, Faisal; Raffetto, Joseph D; Diaz, Jose A; Myers, Daniel D; Ozsvath, Kathleen J; Carman, Teresa L; Lal, Brajesh K; ,
Objectives: Venous leg ulcers (VLU) are the most severe clinical sequelae of venous reflux and post thrombotic syndrome. There is a consensus that ablation of refluxing vein segments and treatment of significant venous obstruction can heal VLUs. However, there is wide disparity in the use and choice of adjunctive therapies for VLUs. The purpose of this study was to assess these practice patterns among members of the American Venous Forum. Methods: The AVF Research Committee conducted an online survey of its own members, which consisted of 16 questions designed to determine the specialty of physicians, location of treatment, treatment practices and reimbursement for treatment of VLUs Results: The survey was distributed to 667 practitioners and a response rate of 18.6% was achieved. A majority of respondents (49.5%) were vascular specialists and the remaining were podiatrists, dermatologists, primary care doctors and others. It was found that 85.5% were from within the USA, while physicians from 14 other countries also responded. Most of the physicians (45%) provided adjunctive therapy at a private office setting and 58% treated less than 5 VLU patients per week. All respondents used some form of compression therapy as the primary mode of treatment for VLU. Multilayer compression therapy was the most common form of adjunctive therapy used (58.8%) and over 90% of physicians started additional modalities (biologics, negative pressure, hyperbaric oxygen and others) when VLUs failed compression therapy, with a majority (65%) waiting less than three months to start them. Medicare was the most common source of reimbursement (52.4%). Conclusions: Physicians from multiple specialties treat VLU. While most physicians use compression therapy, there is wide variation in the selection and point of initiation for additional therapies once compression fails. There is a need for high-quality data to help establish guidelines for adjunctive treatment of VLUs and to disseminate them to physicians across multiple specialties to ensure standardized high-quality treatment of patients with VLUs.